Comparison of performance of no-clean and water-soluble fluxes in fine-pitch flip-chip package / Saif Wakeel - Saif , Wakeel (2021)
The complexity of cleaning caused by miniaturization of electronic packages and the drive towards cost reduction have recently led to the development of no-clean fluxes (NCF). In this study, characterization and effect of two commercial NCF namely NC-1 and NC-2 on the fine pitch flip-chip package were studied. One water soluble flux was also used for comparison. Characterization of these fluxes and their residues were done using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Hygroscopicity of the residue was investigated using water contact angle tests on residue contaminated substrate. Wettability of pre-printed SAC-305 solder on copper substrate was evaluated using the contact angle method. These fluxes were used to fabricate 17x17 mm2 flip-chip packages with fine pitch (150 μm) solder bump and copper pillar based . The formation of interfacial intermetallic compounds (IMCs) was observed using Field emission scanning electron microscopy (FESEM). Die pull strength of solder bumps was evaluated and failure mode was investigated. The quality of the flip-chip assembly was examined by non-destructive methods e.g., 2D radiography and confocal scanning acoustic microscopy (C-SAM). Moisture sensitivity of the package was evaluated using JESD22-A113D (30 oC/60% relative humidity (RH), 192 hours, 3x reflow at 260 oC). Thermal cycling test was performed following JESD22-A104D ( -65 oC to 150 oC) for 2000 cycles. High temperature storage life of package was determined using JESD22-A103C (175 oC) for 2016 hours. Results showed that three carboxylic acids, tertiary amine and ether were present in NC-1. The presence of one carboxylic acid, secondary amide and ether were observed in NC-2. Water soluble flux (WS) showed the presence of carboxylic acid, secondary amine, ether and alcohol. Flux residue showed the presence of carboxylic acid iv and amine for NC-1 and only amide for NC-2. Accelerated evaporation of certain monocarboxylic acids and ether solvent in NCF led to minimal residue as compared to WS. The residue of WS was highly hygroscopic as compared that of NCF’s. Wetting of solder bumps was better for using NC-1 and NC-2 than for WS which could be attributed to flux chemistry. Consequently, higher die pull strength was noticed for NCF immediately after assembly. Average die pull strengths for NCF were 10-17% higher than WS. However, in the moisture sensitivity test, 15.62% of NC-1 and 3.1% of NC-2 treated assemblies exhibited failure. Whereas WS cleaned assembly did not show any failure. During temperature cycling tests, solder bump crack was detected 500 cycles for NC-1 after whereas, crack for NC-2 occurred after 1500 cycles. Cleaned assembly did not show any crack and delamination. Thus, although NCF treated assemblies exhibited higher die pull strength immediately after reflowing. However, they performed poorly in moisture sensitivity and temperature cycling tests.